Learning Management System (LMS) Moodle: Unraveling Its Impact on Accounting Students’ Academic Performance - Jannah, Raodahtul; Sari, Nur Rahmah; Anwar, Puspita Hardianti (DIDAKTIKA, 2023)
The outbreak of covid-19 has caused significant changes in education sector, including the demand to conduct lectures with the assistance of technology. One of the worthly used technologies is the Learning Management System (LMS). This study aims to analyze student perception about factors affecting the use of LMS Moodle and how its use then affects their academic performance. This is a quantitative study adopting personal computer usage model and technology to performance chain model. This study involved 156 accounting students of an Islamic Sate University in Makassar, Indonesia. Data were obtained by questionnaire and analyzed with Structural Equation Modeling (SEM) processed by AMOS. The result shows that of the four variable factors proposed, the task-technology fit factor did not show a positive effect on the use of LMS, while three other variables namely Facilitating Conditions, Social Factors, and Long-Term Consequences show a positive effect on the usage of LMS. Then, Task-Technology Fit and The Use of LMS have a positive effect on Accountant Student’s Academic Performance.Keywords: Accounting students, Academic performance, LMS, Technology